Ageing of InGaN-based LEDs: Effects on internal quantum efficiency and role of defects. Issue 9 (August 2015) - La Grassa, M.; Meneghini, M.; De Santi, C.; Mandurrino, M.; Goano, M.; Bertazzi, F.; Zeisel, R.; Galler, B.; Meneghesso, G.; Zanoni, E.
Abstract: This paper describes the degradation of InGaN-based LEDs submitted to constant current stress; based on combined electroluminescence, photoluminescence and deep-level transient spectroscopy we show that: (i) when submitted to constant current stress, LEDs can show a measurable decrease in the optical power, which is more prominent in the low current regime; (ii) the decrease in optical power is strongly correlated to the increase in the Shockley–Read–Hall recombination coefficient A, as estimated by differential lifetime measurements; (iii) stress induces the increase in the concentration of a trap level, with activation energy between 0.6 and 0.7 eV, which is supposed to be located next to/within the active region. The results suggest that the optical degradation can be ascribed to the increase in non-radiative recombination, rather than to a decrease in carrier injection efficiency. Highlights: We performed constant-current stress on InGaN-based LEDs. The decrease in optical power is correlated with the SRH coefficient. Stress induced the increase in the concentration of a trap level. Optical degradation can be ascribed to the increased non-radiative recombination.